Incorporation of impurity anions into DSP: insights into structure and stability from computer modelling - Lowe, Jennifer; Rohl, Andrew; Gale, Julian; Parkinson, Gordon; Smith, P. (Taylor & Francis Ltd, 2006)
DSP is an important by-product of alumina production via the Bayer process. Under Western Australian processing conditions, the DSP has a sodalite-type structure that can incorporate anions within its framework. This is particularly useful for removal of impurity anions from liquor recycled in the circuit. As a first step to gaining a fundamental understanding of the incorporation process, we have undertaken molecular mechanics calculations to examine the interaction energy between a series of anions and the sodalite framework, as a measure of the affinity of the anions for the sodalite cage. Our calculations predict that the ions have an increased affinity for the cage along the series aluminate, chloride, carbonate, sulfate and hydroxide. These calculations have successfully predicted the trends that we observe from competitive-uptake experiments in our laboratory.